Cuban Counterpoints: The Legacy of Fernando Ortiz - Font, Mauricio A.; Quiroz, Alfonso W. (Lexington Books, 2004)
While Fernando Ortiz's contribution to our understanding of Cuba and Latin America more generally has been widely recognized since the 1940s, recently there has been renewed interest in this scholar and activist who made lasting contributions to a staggering array of fields. This book is the first work in English to reassess Ortiz's vast intellectual universe. Essays in this volume analyze and celebrate his contribution to scholarship in Cuban history, the social sciences—notably anthropology—and law, religion and national identity, literature, and music. Presenting Ortiz's seminal thinking, including his profoundly influential concept of 'transculturation', Cuban Counterpoints explores the bold new perspectives that he brought to bear on Cuban society. Much of his most challenging and provocative thinking—which embraced simultaneity, conflict, inherent contradiction and hybridity—has remarkable relevance for current debates about Latin America's complex and evolving societies.